OP0004 Rheumatoid arthritis occuring after immune checkpoint inhibitors. (15th June 2017) - Belkhir, R; Burel, S Le; Lambotte, O; Mouterde, G; Pertuiset, E; Dunogeant, L; Marabelle, A; Leary, A; Voisin, A-L; Mariette, X
Abstract : Background: Immune checkpoints inhibitors (ICIs) targeting cytotoxic T lymphocyte-associated protein 4 (CTLA-4) and Programmed cell death protein 1 (PD-1) have demonstrated survival improvement in multiple cancers. Immune Related Adverse Events (IrAE) have been described with ipilimumab and anti PD1. Relapse or flare of preexisting auto-immune diseases has been reported but occurrence of new auto-immune diseases seems to be less frequent. A series of 13 patients with non-classified rheumatic IrAE has been published: 9 patients developed non-specific inflammatory arthritis but no seropositive rheumatoid arthritis (RA) and 4 presented with sicca symptoms but did not fulfill criteria for Sjögren syndrome [1]. Objectives: We did a retrospective study for collecting patients who developed seropositive rheumatoid arthritis (RA) after exposition to ICIs. Methods: We used the "Club Rhumatismes et Inflammation (CRI)" network, a section of the French Society of Rheumatology and the Gustave Roussy Cancer Center register of safety of ICI for collecting patients treated with an ICI and who developed symptoms of arthritis with diagnosis of RA. Results: We report 6 patients without any previous rheumatic disease, who developed seropositive rheumatoid arthritis (RA) after exposition to ICIs, all of them after anti-PD1. Conclusions: This is the first description of RA occurring after anti-PD1 treatment for cancer. All cases responded to corticosteroids or with immunosuppressive therapy. This suggests that the PD1/PDL1 axis plays a role in RA pathophysiology. The combined expertise of oncologists, immunologists and rheumatologists is crucial in the successful management of these patients. References: Cappelli LC, Gutierrez AK, Baer AN, et al. Inflammatory arthritis and sicca syndrome induced by nivolumab and ipilimumab. Ann Rheum Dis 2017;76:43–50. Disclosure of Interest: None declared